IMPLEMENTATION OF COMMUNICATIVE-LEADERSHIP FUNCTIONS OF - o‘g‘li, Egamov Jo‘shqin Jumanazar (Research Focus International Scientific Journal, 2026)
This article provides a scientific and theoretical analysis of the processes of implementing the communicative-leadership functions of higher education institution leaders, their main areas of activity, management forms and psychological factors. The study highlights the role of communicative leadership in strategic management, motivation, teamwork, decision- making and the organization of effective communication. It also reveals the distinctive features of democratic, authoritarian and liberal leadership styles and their practical effectiveness in the education system. The role of psychological-pedagogical approaches, teamwork and innovative management mechanisms in developing the communicative competencies of higher education institution leaders is substantiated.